2010
DOI: 10.3892/ijmm_00000523
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting modulation of the diabetic syndrome in sand rats. II. In vivo investigations

Abstract: Abstract. This study deals with the effects of daily intermittent fasting for 15 h upon the development of diabetes in sand rats exposed to a hypercaloric diet. The same pattern of daily intermittent fasting was imposed on sand rats maintained on a purely vegetal diet (control animals). Over the last 30 days of the present experiments, non-fasting animals gained weight, whilst intermittently fasting sand rats lost weight. In this respect, there was no significant difference between control animals and either d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…The glucose [23] in HFD-induced mice and given intermittent fasting treatment resulted in higher insulin levels in mice that were fasted for 12 and 18 h compared to 6 h. However, glucose and β-hydroxybutyric concentrations were higher at 18 h than at 12 h fasting, indicating a decrease in insulin sensitivity and ketogenic state due to extending the fasting duration to 18 h [23]. In line with other studies, intermittent fasting treatment daily for 15 h (17.00-08.00) in 30 days to normal and diabetics sand rats which fed a hypercaloric diet had improved glucose tolerance [26].…”
Section: Discussionsupporting
confidence: 88%
“…The glucose [23] in HFD-induced mice and given intermittent fasting treatment resulted in higher insulin levels in mice that were fasted for 12 and 18 h compared to 6 h. However, glucose and β-hydroxybutyric concentrations were higher at 18 h than at 12 h fasting, indicating a decrease in insulin sensitivity and ketogenic state due to extending the fasting duration to 18 h [23]. In line with other studies, intermittent fasting treatment daily for 15 h (17.00-08.00) in 30 days to normal and diabetics sand rats which fed a hypercaloric diet had improved glucose tolerance [26].…”
Section: Discussionsupporting
confidence: 88%
“…Prolonged daily eating intervals in late hours, usually reserved for sleep, results in overeating and is associated with obesity [ 17 , 18 , 19 ]. Studies in rodents [ 20 ] and in humans [ 10 , 14 , 21 , 22 , 23 , 24 ] have shown that restricting the daily eating window leads to reduced adiposity, systemic inflammation and oxidative stress, improved insulin sensitivity, and longer sleep duration. The temporal aspect of food intake presents as an important modifiable behavior that may decrease predisposition to chronic diseases [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…All statistical analyses were performed by a data scientist in the R software with the RStudio (Version 4.1.0 (22 June 2020), RStudio, Inc. Boston, MA, USA). The sample size was calculated using data from a previous study that was independent of the research reported herein [20].…”
Section: Statical Analyzesmentioning
confidence: 99%